2020
DOI: 10.1093/eurheartj/ehaa696
|View full text |Cite
|
Sign up to set email alerts
|

Standardized exercise training is feasible, safe, and effective in pulmonary arterial and chronic thromboembolic pulmonary hypertension: results from a large European multicentre randomized controlled trial

Abstract: Aims This prospective, randomized, controlled, multicentre study aimed to evaluate efficacy and safety of exercise training in patients with pulmonary arterial (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). Methods and results For the first time a specialized PAH/CTEPH rehabilitation programme was implemented in 11 centres across 10 European countries. Out of 129 enrolled patients, 116 patients (58 vs. 58 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 30 publications
2
39
0
8
Order By: Relevance
“…Randomized controlled studies and controlled cohort studies providing a close inhospital monitoring consistently showed a significant increase in exercise capacity as a result of individually adapted exercise training, a reduction in heart failure symptoms, and an increase in health-related quality of life [131][132][133][134][135][136][137][138][139][140]. Moreover, a reduction in pulmonary vascular resistance and significant increase in cardiac output has been shown [134].…”
Section: Scientific Evidencementioning
confidence: 96%
See 1 more Smart Citation
“…Randomized controlled studies and controlled cohort studies providing a close inhospital monitoring consistently showed a significant increase in exercise capacity as a result of individually adapted exercise training, a reduction in heart failure symptoms, and an increase in health-related quality of life [131][132][133][134][135][136][137][138][139][140]. Moreover, a reduction in pulmonary vascular resistance and significant increase in cardiac output has been shown [134].…”
Section: Scientific Evidencementioning
confidence: 96%
“…On the basis of these data, individualized exercise training in PH-patients can be regarded as an integral part of rehabilitation programs in these patients, provided sufficient medical supervision and expertise is guaranteed. [140].…”
Section: Scientific Evidencementioning
confidence: 99%
“…Aerobic and muscle-strengthening exercise is recognized across healthy populations and health conditions to significantly improve HRQoL as well as cardiovascular, endothelial, metabolic/glandular, muscle structure and function, lung mechanics, mobility and systemic inflammation, fatigue and depressive symptoms, with overall beneficial effect on a wide spectrum of physiological and psychological attributes. Pulmonary rehabilitation is a feasible, safe, and effective [156,157] strategy for improving breathing, exercise tolerance, fatigue, and cough through education, regardless of underlying diagnosis (e.g., ILD, PH). Exercise safety and safety parameters in sarcoidosis-related cardiopulmonary involvement [157,158] and programmatic considerations, and enhancements in this population, are outlined in Tables 6 and 7 [159].…”
Section: Exercise and Physical Activity To Enhance Hrqolmentioning
confidence: 99%
“…Pulmonary rehabilitation is a feasible, safe, and effective [156,157] strategy for improving breathing, exercise tolerance, fatigue, and cough through education, regardless of underlying diagnosis (e.g., ILD, PH). Exercise safety and safety parameters in sarcoidosis-related cardiopulmonary involvement [157,158] and programmatic considerations, and enhancements in this population, are outlined in Tables 6 and 7 [159]. Evidence for the role of physical training in sarcoidosis is limited, but promising, and includes improved exercise capacity [110,111,160], muscle strength [110], and HRQoL [160], and decreased fatigue after a 12-week outpatient physical training intervention.…”
Section: Exercise and Physical Activity To Enhance Hrqolmentioning
confidence: 99%
“…Limited availability and underutilization of exercise training remains a drawback in many specialized PH centers. A recent first multicenter RCT on feasibility, safety, and efficacy of exercise training on PH showed clearly positive results: the primary endpoint -change of 6-min walking distance -significantly improved by 30.7 ± 57.9 m in the training group, while it slightly decreased in the control group (−3.4 ± 25.9 m; p < 0.0001) [17]. Moreover, within this study, a standardized specialized training program, initiated in-hospital, was launched successfully in 10 European countries (including our center in Vilnius).…”
Section: Introductionmentioning
confidence: 99%